Effects of selenium on leaf traits and photosynthetic characteristics of eggplant - Zhang, Lu; Zhao, Xiawei; Wang, Yan; Ma, Xinyu; Li, Haolin; Zhao, Chengzhang (Functional plant biology : FPB, 2025)
The response of leaf traits and photosynthetic characteristics to selenium (Se) application reflects plant adaptation strategies for selenium-enhanced accumulation of photosynthetic products. This study selected eggplant as the research subject and conducted a field experiment to better understand these relationships. This study included three Se treatments, foliar sprays of 0.5 mg L−1 (T1), 1 mg L−1 (T2), and 1.5 mg L−1 (T3), with tap water as the control (CK). The results revealed that T1 and T2 significantly improved leaf traits and photosynthetic characteristics compared to CK, while T3 had a negative effect. Regarding the leaf area–leaf thickness (LA–LT) trade-off relationship, the T2 treatment favoured LA, whereas the CK, T1, and T3 treatments favoured LT, with trade-off values of T3 > T1 > CK. Regarding the net photosynthetic rate–transpiration rate (Pn–Tr) trade-off relationship, the CK treatment favoured Tr, whereas the T1, T2, and T3 treatments favoured Pn, with trade-off values of T2 > T1 > T3. In T1 and T2, the eggplant specific leaf area and Pn showed non-significant and highly significant positive correlations, respectively, and in CK and T3 showed non-significant and highly significant negative correlations, respectively. These results indicate that foliar application of Se at appropriate concentrations can increase crop productivity in semi-arid areas.